Klasifikasi Kematangan Buah Jeruk Berdasarkan Fitur Warna Menggunakan Metode SVM - Muchammad Arief (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2019)
Diverse fruit colors make us sometimes too difficult to determine whether the fruit is in the mature or raw category, therefore in this thesis discussed and explained how to find out the maturity of the fruit by using the SVM method (Support Vector Machine), by taking several image samples oranges by using a digital camera or handheld camera then from the sample the original image will be converted into a greyscale color then from greyscale it will be converted into LAB color in order to find the color A from LAB and R, G from RGB (Red, Green , Blue) then the average value is taken and then classified. From the research, the fruit will be ripe or still raw. From the results of the study, the accuracy of the match was obtained with a percentage of 80% of the data as many as 100 images of oranges. Keywords: Classification of Fruit Maturity Levels, Citra